PHANGS-JWST first results: a global and moderately resolved view of mid-infrared and CO line emission from galaxies at the start of the JWST era - Leroy, Adam K.; Bolatto, Alberto D.; Sandstrom, Karin; Rosolowsky, Erik; Barnes, Ashley T.; Bigiel, F.; Boquien, Médéric; Brok, Jakob S. den; Cao, Yixian; Chastenet, Jérémy; Chevance, Mélanie; Chiang, I.-Da; et al. (The astrophysical journal. Part 2, Letters, 2023)
We explore the relationship between mid-infrared (mid-IR) and CO rotational line emission from massive star-forming galaxies, which is one of the tightest scalings in the local universe. We assemble a large set of unresolved and moderately (∼1 kpc) spatially resolved measurements of CO (1-0) and CO (2-1) intensity, I CO, and mid-IR intensity, I MIR, at 8, 12, 22, and 24 μm. The I CO versus I MIR relationship is reasonably described by a power law with slopes 0.7-1.2 and normalization I CO ∼ 1 K km s−1 at I MIR ∼ 1 MJy sr−1. Both the slopes and intercepts vary systematically with choice of line and band. The comparison between the relations measured for CO (1-0) and CO (2-1) allow us to infer that , in good agreement with other work. The 8 μm and 12 μm bands, with strong polycyclic aromatic hydrocarbon (PAH) features, show steeper CO versus mid-IR slopes than the 22 and 24 μm, consistent with PAH emission arising not just from CO-bright gas but also from atomic or CO-dark gas. The CO-to-mid-IR ratio correlates with global galaxy stellar mass (M ⋆) and anticorrelates with star formation rate/M ⋆. At ∼1 kpc resolution, the first four PHANGS-JWST targets show CO-to-mid-IR relationships that are quantitatively similar to our larger literature sample, including showing the steep CO-to-mid-IR slopes for the JWST PAH-tracing bands, although we caution that these initial data have a small sample size and span a limited range of intensities.
Veröffentlicht: 16. Februar 2023
Gesehen am 28.07.2023